Mobile Learning Kreatif: Meretas Batasan Pembelajaran dalam Mata Kuliah Komunikasi dalam Advokasi: Creative Mobile Learning: Breaking Learning Boundaries in the Course of "Communication in Advocacy” - Setio Ardy Nuswantoro (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2023)
This study develops a mobile learning strategy in the course of "Communication in Advocacy" through the Research and Development (R&D) approach. Literature review indicates that mobile learning can enhance learning motivation, active participation, and accessibility to learning materials. In the context of this course, an integrated approach is needed to enable effective interaction among students and instructors, as well as to foster deep and critical communication skills. This research contributes to the development of mobile learning by designing engaging instructional strategies, ensuring synergistic curriculum integration, maintaining effective communication, and utilizing the latest technologies. The study has the potential to transform the paradigm of learning in the "Communication in Advocacy" course through the creative, critical, and innovative use of mobile learning.